The Implementation Main Values of Character Education Reinforcement in Elementary School (Journal of Primary Education, 2018)
The study aimed to analyze the implementation main values of Character Education Reinforcement on the elementary schools located in Semarang. The study was conducted by using qualitative approach-based descriptive method with case study design. The data gathering methods that had been implemented were observation, semi-structured interview, and documentation study. Then, the data analysis was performed by means of interactive analysis model. For ensuring the data validity, technique-based and resource-based triangulation were performed. The results of the study showed that the implementation main values of Character Education Reinforcement in elementary school on the values of religion and nationalism have been very good and had also become the elementary schools’ culture. However, the independence, mutual cooperation, and integrity have been good but have not been maximally and routinely implemented by all of the elementary schools’ community members. Despite the fact that these values have been integrated into the learning activities in the classroom, the school environment, and the role of surrounding community. The obstacles that have been found are the limited school facility, the violation toward the school’s regulation, the parental abandonment, and the influence of surrounding community. The solutions for overcoming these obstacles might be that the schools should establish cooperation with the parents through the provision of additional prayer equipment in the classroom, the school should play the national anthems more often prior to the beginning of the teaching-learning process, the school should give penalty to the students who violate the school regulation, the school should give awards to the students for their role-modelling activities, the school should give direction to the students’ parents, and the school should provide role model, habituation, and monitoring on the students’ daily activities through their parents.